Unique catanionic vesicles as a potential "nano-Taxi" for drug delivery systems. In vitro and in vivo biocompatibility evaluation - Stagnoli, Antonela Soledad (2016)
We evaluate in vitro and in vivo toxicity and stability in an acidic environment of new vesicles formed by the catanionic surfactant bis(2-ethylhexyl) sulfosuccinate benzyl-n-hexadecyldimethylammonium (AOT-BHD) in order to investigate their potential application as an oral drug delivery system. Unilamellar vesicles were spontaneously formed by dissolving AOT-BHD in water and their toxicity was evaluated through in vitro and in vivo assays. Cell membrane permeability assays (hemolytic activity, Trypan blue assay) and cellular survival or proliferation (MTT assay) were performed. The results showed that only the highest concentration of vesicles tested (2 mg mL-1) diminished the red blood cells' resistance. In vivo toxicity evaluation was carried out on mice through lethal dose 50 (LD50) experiments. The safety for living organisms in doses lower than 0.05 mg mL-1 and the acid pH stability makes our AOT-BHD vesicles a very promising candidate for oral drug delivery.